(untitled) (World Bulletin of Management and Law, 2023)
In great history, nothing passes without a trace. It is preserved in the blood and historical memory of peoples, and is manifested in practical activities. This is why it is important to explain and analyze the history of events in history. Preservation, study and transmission of historical heritage to future generations is one of the most important policy priorities of our country. This article describes the study of information about the social, political and cultural history of Movarannahr and Khorasan in the works of Fasih Khawafi, its significance in historiography and source studies and its analysis.